Edukasi Keuangan Pelajar: Pengenalan Investasi Pada Generasi Z Untuk Mencapai Tujuan Keuangan - Hadi Satria Ganefi; Arief Surya Lesmana (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2024)
Every individual has a good life goal. One of the ways an individual can achieve their goals is through financial success. A person's intelligence in achieving financial success starts from how they can set goals, make financial plans, and manage their finances. Financial education through the introduction of investment to students will reflect financial behaviour that can affect their future welfare level. This community service was carried out at the Islamic boarding school of Tarbiyatul Banin, Dukupuntang, Cirebon Regency, by a Faculty of Economics and Business, Kuningan University team. This service aims to create a young generation that is competent in investment. The methods used in this activity include delivering financial education materials, interactive discussions, and evaluations through quizzes and questionnaires. This activity showed a significant increase in participants' understanding of the basic concepts of investment, capital markets, and the risks associated with investment. These results are expected to provide a positive contribution in preparing a younger generation that is better prepared to face financial challenges in the future.